Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.3758/s13414-014-0733-0
|View full text |Cite|
|
Sign up to set email alerts
|

Attentional control in the attentional blink is modulated by odor

Abstract: Increasing evidence suggests that`aromas have distinctive effects on the allocation of attention in space: Arousing olfactory fragrances (e.g., peppermint) are supposed to induce a more focused state, and calming olfactory fragrances (e.g., lavender) a broader attentional state. Here, we investigate whether odors have similar effects on the allocation of attention in time. Participants performed the attentional blink (AB) task, known to produce a deficit in reporting the second of two target stimuli presented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…The smell of the non-scented room was odor-neutral. Following Colzato et al (2014) , four drops of the appropriate oil were applied to a candle diffuser, diluted in 30 ml of water. Two separate diffusers were used for spreading the two aromas.…”
Section: Methodsmentioning
confidence: 99%
“…The smell of the non-scented room was odor-neutral. Following Colzato et al (2014) , four drops of the appropriate oil were applied to a candle diffuser, diluted in 30 ml of water. Two separate diffusers were used for spreading the two aromas.…”
Section: Methodsmentioning
confidence: 99%
“…Ronconi et al ( 2015 ) also found reduced AB effects when an auditory (but not when a visual) rhythm preceded the RSVP stream in the same frequency as the RSVP items. In general, however, there are also single reports, that the effect of music could not be replicated (Spalek and Di Lollo, unpublished data, as cited by Colzato et al, 2014 ). Further, differences between studies on entrainment and the AB (Zauner et al, 2012 ; Ronconi et al, 2015 ) used rhythms touching alpha.…”
Section: Discussionmentioning
confidence: 97%
“…“De Tuinen™” pure essential oils (De Tuinen Aromatherapie) of peppermint and lavender were used to produce the ambient aromas. Following Colzato et al ( 2014 ) and Sellaro et al ( 2015b ), four drops of the appropriate oil were applied to a candle diffuser, diluted in 30 ml of water. Two separate diffusers were used for spreading the two aromas.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, it has been suggested that stimulating aromas, such as peppermint (Barker et al, 2003 ; Colzato et al, 2014 ; Ho & Spence, 2005 ; Kovar et al, 1987 ; Moss et al, 2008 ; Warm et al, 1991 ; Raudenbush et al, 2001 ; Raudenbush et al, 2009 ; Warm and Dember, 1990 ), lead to a more focused, exclusive attentional state, whereas relaxing aromas, such as lavender (Basevitch et al, 2011 ; Diego et al, 1998 ; Field et al, 2005 ; Lehrner et al, 2005 ; Grimes, 1999 ; Guéguen & Petr, 2006 ; Moss, Cook, Wesnes, & Duckett, 2003 ; Sakamoto et al, 2005 ; Sellaro et al, 2015b ) induce a broader, inclusive attentional state. For instance, research has found that being exposed to peppermint aroma improves memory (Moss et al, 2008 ), sustained visual attention (Warm et al, 1991 ), dual-task performance (Ho & Spence, 2005 ), athletic task performance (Raudenbush et al, 2001 ), and alertness in a driving simulator task (Raudenbush et al, 2009 ), and affects the allocation of attention in time (Colzato et al, 2014 ). In contrast, being exposed to lavender aroma has been found to lessen fatigue (Sakamoto et al, 2005 ), to promote behavior commitment (Grimes, 1999 ), to increase the amount of time customers spend in a restaurant and the amount of purchasing (Guéguen & Petr, 2006 ), and to enhance interpersonal trust (Sellaro et al, 2015b ).…”
Section: Introductionmentioning
confidence: 99%